Exploring differences in psychological well-being and self-regulated learning in university student success - Davis, Sarah K.; Hadwin, Allyson F. (Frontline Learning Research, 2021)
Worldwide, there are increasing concerns about postsecondary students’ mental health and how student success is implicated. Previous research has established psychological well-being and self-regulated learning are important components of student success, however, there is a paucity of research examining the interplay between these factors during a semester-long course. In this study, 118 students in a learning-to-learn elective university course completed nine weekly online planning and reflection tools. Students planned for a study session, completed an academic engagement and a psychological well-being measure, then reflected on a challenge faced and described the strategy chosen to overcome that challenge. Findings revealed (a) students who reported always attaining their goals also reported higher overall psychological well-being, and (b) within-person patterns of psychological well-being and academic engagement over time may affect regulatory responses to challenge or vice versa. Implications for theory, research, and practice are discussed.